2021
DOI: 10.1186/s13731-021-00152-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of corporate entrepreneurship in the financial performance of subsidiaries of Colombian business groups: under environmental dynamism moderation

Abstract: Corporate entrepreneurship creates opportunities in employment, technological advances, value creation, and cultural transformation for entrepreneurial ecosystems, entrepreneurs, governments, economies, and society around the globe. The purpose of this study is to assess the impact of corporate entrepreneurship on the financial performance of subsidiaries in Colombian business groups under the moderating effect of the environmental dynamism, because the relationship between corporate entrepreneurship and finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
0
6
2
Order By: Relevance
“…These findings are in line with previous studies such as Agyapong et al (2021) and Taghizadeh et al (2021) who reported negative interaction between innovation and (market) ED on firm performance. However, this result is in contrast with other studies such as Rodriguez-Pena (2021) andFadlilah et al (2021) who have found significant positive effect of environmental dynamism in the innovation-performance relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in line with previous studies such as Agyapong et al (2021) and Taghizadeh et al (2021) who reported negative interaction between innovation and (market) ED on firm performance. However, this result is in contrast with other studies such as Rodriguez-Pena (2021) andFadlilah et al (2021) who have found significant positive effect of environmental dynamism in the innovation-performance relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…We further screened articles with key words like venture capital, entrepreneurship, SME development and economic growth from 2001-2021 sustaining venture capital and entrepreneurship development. Hunt, 2021;'Ning, 2021;Wennberg, 2021;Chalmers et al, 2021;Riar et al, 2022;Davidsson & Gruenhagen, 2021;Randolph et al, 2021;Aljuwaiber, 2021;Rodríguez-Peña, 2021). Our fast assessment shows a growing interest that most of these articles reflect largely on from US and Europe.…”
Section: B Unequal Geographical and Technological Sector Data Selecti...mentioning
confidence: 98%
“…Breakdown of reviewed articles by year of publication Source: Author's compilation, (2021) In consideration of the reviewed articles published from 2001-2021 as illustrated in Figure VI, above, we discover that 18.2% (22 of 121 articles) appeared in the year 2021, (e.g Lee. N & Andres Rodrıguez-Pose, 2021 Hunt, 2021; 'Ning, 2021; Wennberg, 2021;Chalmers et al, 2021;Riar et al, 2022;Davidsson & Gruenhagen, 2021;Randolph et al, 2021;Aljuwaiber, 2021;Rodríguez-Peña, 2021). Our fast assessment shows a growing interest that most of these articles reflect largely on from US and Europe.…”
mentioning
confidence: 95%
“…Dynamic is a key feature of the environment, which refers to a certain degree of rapid, unpredictable and turbulent changes ( Eisenhardt and Martin, 2000 ). The dynamic environment mainly emphasizes the speed, complexity and way of environmental change ( Rodriguez-Pea, 2021 ), and the uncertainty and unpredictability that it brings ( Rosenbusch et al, 2013 ). Scholars generally divide environmental dynamics into technological development dynamics and market demand dynamics, which mainly include unpredictability of customers, market trend change rates, peer competitors, business growth opportunities, R&D process ( Rodriguez-Pea, 2021 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The dynamic environment mainly emphasizes the speed, complexity and way of environmental change ( Rodriguez-Pea, 2021 ), and the uncertainty and unpredictability that it brings ( Rosenbusch et al, 2013 ). Scholars generally divide environmental dynamics into technological development dynamics and market demand dynamics, which mainly include unpredictability of customers, market trend change rates, peer competitors, business growth opportunities, R&D process ( Rodriguez-Pea, 2021 ). In addition, environmental dynamics are related to uncertainty, which weakens the employer’s ability to predict events and their impact on the organization ( Lumpkin and Dess, 2001 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%